Comparative distribution of Mycobacterium avium subspecies paratuberculosis in the target and non-target tissues of goats and sheep population in India - VORRA, J; SINGH, S V; SINGH, A V; SINGH, P K; SOHAL, J S (The Indian Journal of Animal Sciences, 2011)
Target and non-target tissues of 41 goats and 20 sheep (farm and farmer’s stocks) were screened by culture and peR, to know the distribution of MAP in different tissues and organs. Species-wise prevalence of MAP was 42.5 and 40.0% in goats and sheep, respectively, and was 48.1 and 39.3% in animals (goats and sheep) from farm and farmer’s stocks, respectively. Of the 215 tissues screened by culture, 47.9% were positive for MAP. Prevalence was 50.8 and 40.0% in tissues of goats and sheep from farm stock, respectively and 60.0 and 44.2% in tissues of young and adult animals, respectively. Tissues-wise, 42.5 and 53.8% farm animals were positive in culture of mesenteric lymph nodes (MLN) and intestine tissues, respectively, whereas, 37.5 and 41.1 %, respectively in farmer’s animals. Screening of supramammary lymph nodes (SMLN) revealed that, 52.5 and 43.1%were positive from farm and fanner’s animals, respectively. Inflamed SMLN from farm stocks showed higher infectivity. MAP was recovered from 73.6, 64.2, and 54.50/0 tissues of uterus, udder and testes, respectively, in fann stocks. Of the MAP cultured from goats, 82.0% were pauci and 17.9% multi-bacillary and from sheep, all the cultures were pauci bacillary. Majority of colonies appeared between 45 and 120 days post inoculation. Decontaminated pellets from tissues and MAP cultures were processed for DNA isolation and screened by IS900 PCR. Positive DNA samples on amplification yielded specific 229bp band from pellets of intestine, MLN, SMLN, udder, uterus and testes. From MAP cultures, 4 of 13 DNA were amplified. Protoplasmic (PPA) antigen from MAP ’Bison type’ strain cultured from a terminal case of JD in goat was used in ELISA. Study revealed that MAP was distributed widely in target and non-target tissues of goats and sheep. Of the 3 test used, culture of tissues was most sensitive. This is the first report of recovery of MAP from non-target tissues of goats and sheep in India. Â